The last word eaudiobook A novel. - Griffiths, Elly (Harbinder Kaur, 2024)
Words turn deadly with an unlikely detective duo on the case of a murdered obituary writer in this literary mystery from the internationally bestselling author of the Ruth Galloway series. Perfect for fans of Richard Osman and the Thursday Murder Club. Natalka and Edwin are perfect if improbable partners in a detective agency. At eighty-four, Edwin regularly claims that he's the oldest detective in England. He is a master at surveillance, deploying his age as a cloak of invisibility. Natalka, Ukrainian-born and more than fifty years his junior, is a math whizz, who takes any cases concerning fraud or deception. Despite a steady stream of minor cases, Natalka is frustrated. She loves a murder, as she's fond of saying, and none have come the agency's way. That is until local writer Melody Chambers dies. Melody's daughters are convinced that their mother was murdered. Edwin thinks that Melody's death is linked to that of an obituary writer who predeceased many of his subjects. Edwin and Benedict go undercover to investigate and are on a creative writing weekend at isolated Battle House when another murder occurs. Are the cases linked and what is the role of a distinctly sinister book group attended by many of writers involved? By the time Edwin has infiltrated the group, he is in serious danger... Seeking professional help, the investigators turn to their friend, detective Harbinder Kaur, and find that they have stumbled on a plot that is stranger than fiction.